2012
DOI: 10.1007/s10899-012-9324-y
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Participation and Problem Gambling Severity among Rural and Peri-Urban Poor South African Adults in KwaZulu-Natal

Abstract: Poor South Africans are significantly poorer and have lower employment rates than the subjects of most published research on gambling prevalence and problem gambling. Some existing work suggests relationships between gambling activity (including severity of risk for problem gambling), income, employment status and casino proximity. The objective of the study reported here is to establish the prevalence of gambling, including at risk and pathological gambling, and the profile of gambling activities in two sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…As the duration of senior high school is three years, second year students may have thought they have plenty of time to spare and may use this time to engage in various social activities, including gambling. In all cases, high frequency gamblers also had a positive attitude towards gambling and considered gambling to be a positive experience compared to non/low frequency gamblers (10,39).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As the duration of senior high school is three years, second year students may have thought they have plenty of time to spare and may use this time to engage in various social activities, including gambling. In all cases, high frequency gamblers also had a positive attitude towards gambling and considered gambling to be a positive experience compared to non/low frequency gamblers (10,39).…”
Section: Discussionmentioning
confidence: 95%
“…While many western countries have comprehensive data on the impact of gambling on the population, little is known about gambling in African countries, especially among young people. One of the few studies that has reported gambling impact data in Africa, done in South Africa, reported 2% prevalence of problem gambling and a further 10% being considered at risk (10). Street youth are turning to gambling as a means of earning money in several African countries including Ghana where university students were introducing gambling to the local adolescents, creating problems for the community (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of sports-betting in our study population is comparable to that from a study in the United States [16], although this was a student population. However, the frequency in our study population is only half of that demonstrated in a South Africa population [17]. This study in South Africa was conducted among a general adult population, mostly low income poor population.…”
Section: Discussionmentioning
confidence: 52%
“…In this regard, a recent survey conducted in Uganda found that 39% of respondents reported that they were aware of minors who engaged in gambling activities ( 42 ). Besides the influence of peers and aggressive marketing efforts from the gambling sector ( 42 ), GD and associated problems sometimes trace their roots in a family setting where young people are introduced to gambling at a young age ( 34 ). In a study conducted in South Africa 13% of the gamblers had experienced gambling problems in their families while they were younger (i.e., before young adulthood) ( 34 ).…”
Section: Gambling Among Young People In Ssamentioning
confidence: 99%